2019
DOI: 10.1186/s12964-019-0344-4
|View full text |Cite
|
Sign up to set email alerts
|

PRMT5 enhances tumorigenicity and glycolysis in pancreatic cancer via the FBW7/cMyc axis

Abstract: Background The epigenetic factor protein arginine methyltransferase 5 (PRMT5) has been reported to play vital roles in a wide range of cellular processes, such as gene transcription, genomic organization, differentiation and cell cycle control. However, its role in pancreatic cancer remains unclear. Our study aimed to investigate the roles of PRMT5 in pancreatic cancer prognosis and progression and to explore the underlying molecular mechanism. Methods Real-time PCR, im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 60 publications
1
70
0
Order By: Relevance
“…PRMT5 plays crucial roles in carcinogenesis (39,40) and autoimmune pathogenesis (8). Although multiple mechanisms tightly control PRMT5 expression in nontransformed T cells (9), uncontrolled PRMT5 expression is a hallmark of hematologic and solid oncogenic tumors (41)(42)(43)(44)(45). The driver role of PRMT5 in cancer has led to efforts to develop PRMT5-selective inhibitors as a therapy for solid and hematologic cancers that are currently being tested for safety and efficacy (Clinicaltrials.gov, registration ID: NCT03573310, NCT03854227, NCT02783300, NCT03614728).…”
Section: Discussionmentioning
confidence: 99%
“…PRMT5 plays crucial roles in carcinogenesis (39,40) and autoimmune pathogenesis (8). Although multiple mechanisms tightly control PRMT5 expression in nontransformed T cells (9), uncontrolled PRMT5 expression is a hallmark of hematologic and solid oncogenic tumors (41)(42)(43)(44)(45). The driver role of PRMT5 in cancer has led to efforts to develop PRMT5-selective inhibitors as a therapy for solid and hematologic cancers that are currently being tested for safety and efficacy (Clinicaltrials.gov, registration ID: NCT03573310, NCT03854227, NCT02783300, NCT03614728).…”
Section: Discussionmentioning
confidence: 99%
“…In the procession of tumors, due to the nutritional supply disorder caused by abnormal oxygen and blood vessels, tumor cells have to undergo metabolic reprogramming to maintain their proliferation, and the main characterization of metabolic reprogramming is aerobic glycolysis. 9 A previous study revealed that PRMT5 could intensify the glycolysis of pancreatic cancer, 10 but there was no study on the effect of PRMT5 on the metabolism of BC and its mechanism. Liver X receptor α (LXRα), as a member of the nuclear receptor family, plays an important role in glucose metabolism and inflammatory response, 11 and in recent years, a study has found its important role in the development and progression of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…21 More recently, PRMT5 was demonstrated that lead to FBW7 expression to promote tumorigenesis in pancreatic cancer. 14 ling, 24 and EGF-induced nuclear translocation of SHCBP1 directly increased acetylation of β-catenin to enhanced NSCLC cellular stemness, 25 which is suggested that EGFR signalling can drive β-catenin activation via various routes. In this study, we provide a novel F I G U R E 2 PRMT5 promotes cell proliferation in pancreatic cancer cells and tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…13 In addition, PRMT5 was proved to inhibit the tumour suppressor FBW7, resulting in increasing c-Myc levels to promote the proliferation of and aerobic glycolysis in pancreatic cancer cells. 14 In this study, we examined the roles of PRMT5 in pancreatic cancer and elucidated the underlying mechanism. Our data showed that PRMT5 promoted cell proliferation, migration and invasion in pancreatic cancer cells, and promoted tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%